Cooperative Control Strategy of Optical Storage System Based on an Alternating Sequence Filter - Zifen Han; Yun Zhang; Biao Tian; Yi Fan; Chao Zhang; Huijuan Wu (Energies)
Due to photovoltaic (PV) power generation depending on the environment, its output power is volatile, and effectively dealing with its power fluctuation has become a key concern. Aiming at this problem, this article presents an optical storage cooperative control technology based on an Alternating Sequence Filter (ASF), which controls the power management of the Energy Storage System (ESS) consisting of a vanadium redox battery, battery, and supercapacitor. Firstly, an ASF is designed to stabilize the PV power generation by alternating sequence and improve system response speed. Secondly, according to the output signal of the filter, the charge and discharge of the three energy storage units are dynamically adjusted, and the power fluctuation is compensated in real-time to improve the system stability and conversion efficiency. Finally, the simulation results of actual illumination show that the control strategy calls the ESS to stabilize the power fluctuation, so that the power of the direct current bus is stabilized at about 15 kw, and the fluctuation is maintained between −4.48% and 4.05%. The strategy significantly reduces power fluctuation and improves the dynamic response ability and energy storage utilization of the system.